The lifetime risk of developing type II diabetes in an urban community in Mumbai: findings from a ten-year retrospective cohort study - Palak Sharma; T. R. Dilip; Udaya Shankar Mishra; Anjali Kulkarni (BMC, 2023)
Abstract Background Incidence and prevalence do not capture the risk of developing diabetes during a defined period and only limited evidence exists on the lifetime risk of diabetes based on longer and continuous follow-up studies in India. Lacunae in evidence on lifetime risk can be attributed primarily to the absence of comprehensive and reliable information on diabetes incidence, mortality rates and lack of longitudinal studies in India. In light of the scarcity of evidence in India, the objective of this study was to estimate the incidence of diabetes and its lifetime risk in an urban community of Mumbai. Methods The research study utilized data which is extracted from the electronic medical records of beneficiaries covered under the Contributory Health Service Scheme in Mumbai. The dataset included information on 1652 beneficiaries aged 40 years and above who were non-diabetic in 2011-2012, capturing their visit dates to medical center and corresponding laboratory test results over a span ten years from January, 2012- December, 2021. Survival analysis techniques are applied to estimate the incidence of diabetes. Subsequently, the remaining life years from the life table were utilized to estimate the lifetime risk of diabetes for each gender, stratified by age group. Results A total of 546 beneficiaries developed diabetes in ten years, yielding an unadjusted incidence rate of 5.3 cases per 1000 person-years (95% CI: 4.9- 5.8 cases/ 1000 person years). The age-adjusted lifetime risk of developing type II diabetes in this urban community is estimated to be 40.3%. Notably, males aged 40 years and above had 41.5% chances of developing diabetes in their lifetime as compared to females with a risk of 39.4%. Moreover, the remaining lifetime risk of diabetes decreased with advancing age, ranging from 26.4% among 40-44 years old to 4.2% among those age 70 years and above. Conclusion The findings stress the significance of recognizing age specific lifetime risk and implementing early interventions to prevent or delay diabetes onset and to focus on diabetes management programs in India.